Analysis of Factors Affecting Intention to Donate Money with the Theory of Planned Behaviour and UTAUT Approach - Agung Yulianto; Abdul Rohman; Surya Rahardja (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
Islamic economic instruments in the Indonesian economic system play an important role, such as waqf which can provide many benefits to society. Waqf instruments continue to innovate, where previously they were limited to land or buildings, now there are waqf instruments in the form of money. However, cash waqf is considered to be still not optimal because the potential of existing waqf is very far from the waqf that can be collected. This study aims to determine whether there is an influence of attitudes, subjective norms, performance expectations and social influences on intentions to endow money. The population of this study is the Muslim community in the city of Semarang. By taking a sample of 150 respondents by purposive non-random sampling. The data collection used a Googleform questionnaire, the data analysis method used SEM (Structural Equation Model) based on the SmartPLS 3.0 application. The results showed that the research model used was valid and reliable so that it was used properly. Based on the hypothesis test, the result is that attitude has a positive and significant direct effect on the intention of cash waqf. Subjective norms have a positive and not significant direct effect on cash waqf intentions. Performance Expectation has a positive and significant effect on cash waqf intentions. Social influence has a positive and insignificant effect on cash waqf intentions. The conclusion from this study is that the higher the attitude factor in a person which comes from beliefs in behaviour, the higher the intention of cash waqf, and the higher the performance expectation factor which comes from the level of confidence in obtaining profits in behaviour, the higher the intention of cash waqf. Likewise, subjective norm factors originating from social pressure have no influence on cash waqf intentions and social influence factors originating from social pressure in perceiving the use of the system have no influence on cash waqf intentions.